Public Sector Procurement in Ghana (Volume 1) - Oswald Atiga (Public Sector Procurement in Ghana (Volume 1), 2024)
The aftermath of Ghana’s public procurement reforms from the late 1990s and early 2000s championed by the World Bank culminated in the promulgation of the Country’s Public Procurement Act, Act 663 of 2003 as amended. This book entitled ‘Public Sector Procurement in Ghana, (Volume 1)’, seeks to add to the existing discourse on public procurement conduct within the country’s public procurement space. Chapter one of this book provides explanations of terms commonly used within the public procurement function. The second chapter introduces public procurement as a concept whilst chapter three discusses the procurement principles. Additionally, chapter four discusses the composition and role of the public procurement board within the context of the public procurement function. The rest of the chapters discuss the public procurement structures, procurement planning, the procurement cycle, procurement methods, the tendering procedures, negotiations in public procurement, awarding and management of contracts, the procurement review process under Ghana’s procurement law, the disposal of obsolete stores, plant, and equipment, sustainability in public procurement and special topics in public procurement. This book targets both public procurement practitioners and students who find themselves within the public procurement spectrum.